Identification of genetic and chemical modulators of zebrafish mechanosensory hair cell death. - Kelly N Owens; Felipe Santos; Brock Roberts; Tor Linbo; Allison B Coffin; Anna J Knisely; Julian A Simon; Edwin W Rubel; David W Raible (PLoS Genetics, 2008)
Inner ear sensory hair cell death is observed in the majority of hearing and balance disorders, affecting the health of more than 600 million people worldwide. While normal aging is the single greatest contributor, exposure to environmental toxins and therapeutic drugs such as aminoglycoside antibiotics and antineoplastic agents are significant contributors. Genetic variation contributes markedly to differences in normal disease progression during aging and in susceptibility to ototoxic agents. Using the lateral line system of larval zebrafish, we developed an in vivo drug toxicity interaction screen to uncover genetic modulators of antibiotic-induced hair cell death and to identify compounds that confer protection. We have identified 5 mutations that modulate aminoglycoside susceptibility. Further characterization and identification of one protective mutant, sentinel (snl), revealed a novel conserved vertebrate gene. A similar screen identified a new class of drug-like small molecules, benzothiophene carboxamides, that prevent aminoglycoside-induced hair cell death in zebrafish and in mammals. Testing for interaction with the sentinel mutation suggests that the gene and compounds may operate in different pathways. The combination of chemical screening with traditional genetic approaches is a new strategy for identifying drugs and drug targets to attenuate hearing and balance disorders.